2021
DOI: 10.1200/jco.2021.39.15_suppl.4046
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of perioperative chemotherapy + avelumab in locally advanced gastroesophageal adenocarcinoma: Preliminary results.

Abstract: 4046 Background: Perioperative chemotherapy improves cure rate in locally advanced gastroesophageal adenocarcinoma (GEA), and immune checkpoint inhibitors are active at the metastatic stage. This trial tests the hypothesis that the addition of avelumab to perioperative chemotherapy will increase the major pathologic response (MPR) rate in comparison with historical controls. Methods: Phase II study of avelumab + chemotherapy (docetaxel, cisplatin and 5-FU or mDCF) given every 2 weeks for 4 cycles before and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Based on preliminary data, the neoadjuvant ICI-based therapy led to good outcomes in pathological responses, especially in MSI-H or PD-L1 positive patients. This was consistent with several recent phase I/II single-armed studies in the 2021 ASCO annual meeting, which used ICI plus chemotherapy to treat cT3-4 or N+ gastric cancer patients and achieved >90% R0 resection rates, 0-25% CPR, and 22-42% MPR [26][27][28][29][30][31] . Compared with these studies, our trial recruited patients with more advanced cancer, all being cT4N+, 56% initially unresectable cT4bN+, and 64% Lauren's diffused type patients.…”
Section: Discussionsupporting
confidence: 89%
“…Based on preliminary data, the neoadjuvant ICI-based therapy led to good outcomes in pathological responses, especially in MSI-H or PD-L1 positive patients. This was consistent with several recent phase I/II single-armed studies in the 2021 ASCO annual meeting, which used ICI plus chemotherapy to treat cT3-4 or N+ gastric cancer patients and achieved >90% R0 resection rates, 0-25% CPR, and 22-42% MPR [26][27][28][29][30][31] . Compared with these studies, our trial recruited patients with more advanced cancer, all being cT4N+, 56% initially unresectable cT4bN+, and 64% Lauren's diffused type patients.…”
Section: Discussionsupporting
confidence: 89%
“…The selection process and reasons for study exclusion are shown in Figure 1. Among the 27 studies, 8 trials with 221 patients examined nICRT (14-21), 19 trials with 588 patients examined nICT (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Except one twoarms trial (33), all included studies were single-arm trials.…”
Section: Eligible Studiesmentioning
confidence: 99%
“…The frequently adopted RT dose in studies of nICRT was 41.4Gy in 23 fractions (4/8). The median patient age were 63 years (interquartile range [IQR], 62-64 years) and 62 years (IQR, 61-64) for patients receiving nICRT and nICT, respectively; and the median sample sizes were 26 participants (IQR, [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] and 28 participants (IQR, 20-41), respectively. The main characteristics and outcomes of studies are presented in Tables 1, 2.…”
Section: Eligible Studiesmentioning
confidence: 99%
“…Our observations appear consistent with other small prospective trials reported to date in which ICIs have been incorporated into perioperative chemotherapy for molecularly unselected patients with GC. [32][33][34] Ongoing phase III trials randomizing patients with GC receiving perioperative chemotherapy to the addition of an ICI or placebo may validate acceptable toxicities. 35,36 Despite the dramatic responses to ICIs demonstrated in MSI-H tumors, the adoption of MSI/dMMR testing in the clinical setting remains a challenge.…”
Section: Discussionmentioning
confidence: 99%